Tanggung Gugat Penyelenggara Jalan terhadap Kecelakaan Lalu Lintas Akibat Jalan Rusak : Studi Hukum Perdata - , Faradila Faradila; Nur Arifudin; Nomensen Freddy Siahaan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This is related to the rights of traffic accident victims regulated in Article 240 of Law 22 of 2009 concerning Road Traffic and Transportation "traffic accident victims have the right to receive compensation from the party responsible and are entitled to insurance compensation from the insurance company". Article 1365 of the Civil Code, every person who commits an unlawful act is obliged to compensate for the losses arising from his or her mistake. In fact, many accidents occur due to damaged roads in Samarinda City, so this is one of the factors causing traffic accidents.The aim of this research is to answer two things. First, to find out and examine unlawful acts by the authorities in cases of traffic accidents due to damaged roads. Second, we want to know and examine the legal responsibilities of road operators. In this part of the research, we review and explore the relevant laws that regulate and are relevant to claims for compensation against road operators by victims of traffic accidents due to damaged roads.The results obtained from this research are as follows: 1) In this case, the occurrence of traffic accidents in terms of the last 5 years continues to show a significant increase, which means that the government has not maximally provided the community's rights, namely to have good roads. One of the causes of accidents is damaged roads, but to date no member of the public has filed a civil lawsuit against the government for compensation for the pain they suffered. 2) The government's regulations and efforts to provide protection for road users are sufficient, but they are not implemented optimally, in fact the public has never been given an appeal to demand their rights to receive good roads.